The Role of Guidance and Counseling in Overcoming Social Pathology Through the Implementation of Social Rehabilitation - Dea Audina Siregar; Arie Ernezh Rumapea; Melisa Devianti Manalu; Widia Gultom (Era Scientific Publisher, 2026)
Social pathology, including juvenile delinquency, substance abuse, violence, and other forms of deviant behavior, remains a significant social issue that negatively affects individual well-being and community stability. Social rehabilitation has been widely recognized as an important approach for restoring the psychological, social, and behavioral functioning of individuals experiencing such problems. In this context, guidance and counseling play a strategic role in facilitating behavioral change, strengthening resilience, and supporting successful social reintegration. This study aims to examine the role of guidance and counseling in addressing social pathology through social rehabilitation programs. The study employed a qualitative literature review approach by analyzing relevant scholarly publications published between 2016 and 2026. Literature sources were collected from scientific books, national and international journal articles, and other credible academic publications related to social pathology, social rehabilitation, and counseling interventions. Data were analyzed using thematic content analysis to identify major themes and patterns across the reviewed literature. The findings indicate that guidance and counseling contribute significantly to social rehabilitation through individual counseling, group guidance, group therapy, social support interventions, peer counseling, Cognitive Behavioral Therapy (CBT), and collaborative ecosystem-based approaches involving families, schools, and communities. These interventions help individuals improve self-awareness, develop adaptive coping skills, strengthen social functioning, reduce maladaptive behaviors, and enhance readiness for community reintegration. Furthermore, the literature highlights the importance of integrating psychological, social, moral, and spiritual dimensions into rehabilitation processes to achieve sustainable recovery outcomes. The study concludes that guidance and counseling should be positioned as a core component of social rehabilitation programs and that collaborative, holistic, and evidence-based interventions are essential for effectively addressing social pathology in contemporary society.